2019
DOI: 10.3389/fgene.2019.00751
|View full text |Cite
|
Sign up to set email alerts
|

The Identification and Analysis of mRNA–lncRNA–miRNA Cliques From the Integrative Network of Ovarian Cancer

Abstract: Ovarian cancer is one of the leading causes of cancer mortality in women. Since little clinical symptoms were shown in the early period of ovarian cancer, most patients were found in phases III–IV or with abdominal metastasis when diagnosed. The lack of effective early diagnosis biomarkers makes ovarian cancer difficult to screen. However, in essence, the fundamental problem is we know very little about the regulatory mechanisms during tumorigenesis of ovarian cancer. There are emerging regulatory factors, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 91 publications
(106 reference statements)
2
17
0
Order By: Relevance
“…However, direct lncRNA interactions with protein or mRNA are also observed, for example, WDR7-7 lncRNA with mRNA of the GPR30 gene [ 17 ]. Moreover, large-scale regulatory networks have already been outlined for lncRNA, mRNA, and miRNA in cancer cells [ 18 , 19 , 20 ]. LncRNAs add new layers to regulatory networks and deepen our understanding of the mechanisms of oncogenesis, which is necessary for a constructive approach to diagnosis, prognosis on cancer progression, response to therapy, as well as for the search for new therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…However, direct lncRNA interactions with protein or mRNA are also observed, for example, WDR7-7 lncRNA with mRNA of the GPR30 gene [ 17 ]. Moreover, large-scale regulatory networks have already been outlined for lncRNA, mRNA, and miRNA in cancer cells [ 18 , 19 , 20 ]. LncRNAs add new layers to regulatory networks and deepen our understanding of the mechanisms of oncogenesis, which is necessary for a constructive approach to diagnosis, prognosis on cancer progression, response to therapy, as well as for the search for new therapeutic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that lncRNAs serve as miRNAs spongers in implication in OC. [19][20][21] miRNAs could be putative oncogenic or tumor-suppressive factors by acting as key modulators of gene expression, and are important targets of lncRNAs. 22,23 The putative miRNA targets of LEMD1-AS1 were then investigated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Created with Biorender.com. (104,105). This network promotes the acquisition of cellular phenotypes such as migration, invasion, angiogenesis, and VM (Figure 3).…”
Section: Lncrnas-mirnas-mrnas Regulation Network Of the Vm And Theirmentioning
confidence: 99%